(Conflict Resolution of Irrigation Development: Case Study in Ibu subdistrict of West Halmahera District) - Sahabu, Budi; ., Saharuddin; M. Kolopaking, Lala (Sodality: Jurnal Sosiologi Pedesaan, 2017)
ABSTRACTThe objective of this research is to understand the conflict resolution of dam and irrigation development in three subdistrict villages of Ibu Halmahera Barat district 2013. This research uses analysis of dispute style (AGATA) in the form of: avoidance, accommodating, compromise, competitive, and collaboration. The results showed that there are two styles of conflict that is avoid and competitive style. Both style of disputes are transformed into a compromise style after the opposing party offers negotiation of land compensation. Based on this it can reduce the two parties, so that the mediator easily deal with the conflict. The settlement path is through mediation and facilitation by bringing the two conflicting parties together with the mediator of West Halmahera people’s parliament. The decision taken is to stop the construction of dam and irrigation channels under construction. The decision, in addition to reducing the escalation of tensions, also to anticipates violet conflict between the two parties (the pros and cons of development).Keyword: Conflict resolution, irrigation development, dispute styleABSTRAKPenelitian ini bertujuan memahami resolusi konflik pembangunan bendung dan irigasi di tiga desa kecamatan Ibu kabupaten Halmahera Barat pada tahun 2013. Penelitian ini mengunakan analisis gaya bersengketa (AGATA) yang berupa: saling menghindar, akomodatif, kompromistis, kompetitif, dan kolaborasi. Hasil penelitian menunjukan bahwa terdapat dua gaya berkonflik yaitu gaya menghindar dan kompotisi. Kedua gaya bersengketa tersebut berubah menjadi gaya berkompromi setelah pihak lawan (kontra) menawarkan negosiasi ganti rugi lahan. Berdasarkan hal tersebut dapat mengurangi eskalasi ketegangan antar kedua belah pihak, sehingga pihak mediator dengan mudah menangani konflik. Jalur penyelesaian yang ditempuh yaitu melalui mediasi dan fasilitasi dengan cara mempertemukan kedua belah pihak yang berseteru dengan mediator pihak dewan perwakilan rakyat daerah Halmahera Barat. Keputusan yang diambil adalah memberhentikan proyek pembangunan bendung dan saluran irigasi yang sedang dibangun. Keputusan tersebut, selain mengurangi eskalasi ketegangan juga mengantisipasi terjadinya konflik kekerasan antar kedua belah pihak (pihak pro dan kontra pembangunan).Kata kunci: Resolusi konflik, pembangunan irigasi, gaya bersengketa